Developmental regulation of CYP3A4 and CYP3A7 in Chinese Han population. Issue 6 (December 2016) - He, Hang; Nie, Ya-Li; Li, Jiang-Feng; Meng, Xiang-Guang; Yang, Wei-Hong; Chen, Yu-Long; Wang, Shu-Jie; Ma, Xiaochao; Kan, Quan-Cheng; Zhang, Li-Rong
Abstract: CYP3A4 and CYP3A7 are generally served as the major adult and fetal liver forms, respectively, and exhibited a developmental switch during liver maturation. The objective of this study was to explore the potential mechanisms associated with the developmental switch of CYP3A4 and CYP3A7 in the Chinese Han population. We analyzed CYP3A4/7, nuclear receptors, and epigenetic modifications in human liver samples. We found that the expression levels of CYP3A4 mRNA in adults were significantly higher than the levels in fetus. In contrast, CYP3A7 mRNA expression reached a maximal level at an estimated gestational age of 25 weeks and then substantially decreased during the first year after birth. We also found that the expression level of hepatocyte nuclear factor 4 alpha (HNF4A) was most associated with CYP3A4 expression in adult liver; whereas the expression level of glucocorticoid receptor (GR) was intensively correlated with CYP3A7 expression in fetal liver. Furthermore, we illustrated the dynamic changes of H3K4me2 and H3K27me3 in the developmental switch of CYP3A7 and CYP3A4. In summary, our data suggested that HNF4A and GR, and epigenetic changes of H3K4me2 and H3K27me3 are associated with the ontogenic expressions of CYP3A4/3A7 in the livers of the Chinese Han population. Graphical abstract: